2007
DOI: 10.1038/sj.jp.7211807
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress in parents of children with severe congenital heart disease: the impact of prenatal versus postnatal diagnosis

Abstract: Objective: The purpose of the study was to evaluate coping and psychological functioning of parents of children prenatally or postnatally diagnosed with congenital heart disease.Study Design: Parents of 10 infants prenatally diagnosed by fetal echocardiogram and 7 infants postnatally diagnosed with severe congenital heart disease completed the Brief Symptom Inventory (BSI) at the time of diagnosis, at the time of birth and 6 months after birth. Prenatal and postnatal groups were compared to each other and to B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
104
2
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(121 citation statements)
references
References 19 publications
9
104
2
2
Order By: Relevance
“…Additionally, despite some variability in the time elapsed since the diagnosis until the delivery of questionnaires, our results on psychological distress after a DCA are similar to previous studies with assessments at one week (Brosig et al, 2007), one month (Doherty et al, 2009), and 8-10 weeks (Brisch et al, 2003) after the diagnosis. As such, we consider that this variability does not significantly compromise our results.…”
Section: Strengths and Limitationssupporting
confidence: 79%
See 2 more Smart Citations
“…Additionally, despite some variability in the time elapsed since the diagnosis until the delivery of questionnaires, our results on psychological distress after a DCA are similar to previous studies with assessments at one week (Brosig et al, 2007), one month (Doherty et al, 2009), and 8-10 weeks (Brisch et al, 2003) after the diagnosis. As such, we consider that this variability does not significantly compromise our results.…”
Section: Strengths and Limitationssupporting
confidence: 79%
“…However, the existent studies showed that adjustment in the early post-diagnosis stage predicted parental adjustment in later evaluations (e.g., six months after the birth of the infant, Skari et al, 2006). Furthermore, even where there was a decrease in the levels of psychopathological symptoms over time, they tended to keep significantly higher than the normative values (Brisch et al, 2003;Brosig et al, 2007). Similar results were found in a longitudinal study on the impact of a perinatal loss in maternal psychopathological symptoms.…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…However, other studies did not find gender differences in levels of psychological distress (Brosig et al, 2007).…”
Section: Psychological Distressmentioning
confidence: 86%
“…Skari et al (2006) found that six weeks after birth, parents of infants with a surgically correctable CA had higher levels of psychological distress than parents of healthy infants. Comparing their data to normative data, Brosig, Whitstone, Frommelt, Frisbee, and Leuthner (2007) found that parents of children with congenital heart disease had higher levels of psychological distress at the time of their child's birth. Aite et al (2003) also found higher levels of anxiety in parents of infants with a surgically correctable CA.…”
Section: Psychological Distressmentioning
confidence: 99%